Impact of climate change on heat-related mortality in Jiangsu Province, China - Chen, Kai; Horton, Radley M.; Bader, Daniel A.; Lesk, Corey; Jiang, Leiwen; Jones, Bryan; Zhou, Lian; Chen, Xiaodong; Bi, Jun; Kinney, Patrick L. (Environmental pollution (1987), 2017)
A warming climate is anticipated to increase the future heat-related total mortality in urban areas. However, little evidence has been reported for cause-specific mortality or nonurban areas. Here we assessed the impact of climate change on heat-related total and cause-specific mortality in both urban and rural counties of Jiangsu Province, China, in the next five decades. To address the potential uncertainty in projecting future heat-related mortality, we applied localized urban- and nonurban-specific exposure response functions, six population projections including a no population change scenario and five Shared Socioeconomic Pathways (SSPs), and 42 temperature projections from 21 global-scale general circulation models and two Representative Concentration Pathways (RCPs). Results showed that projected warmer temperatures in 2016–2040 and 2041–2065 will lead to higher heat-related mortality for total non-accidental, cardiovascular, respiratory, stroke, ischemic heart disease (IHD), and chronic obstructive pulmonary disease (COPD) causes occurring annually during May to September in Jiangsu Province, China. Nonurban residents in Jiangsu will suffer from more excess heat-related cause-specific mortality in 2016–2065 than urban residents. Variations across climate models and RCPs dominated the uncertainty of heat-related mortality estimation whereas population size change only had limited influence. Our findings suggest that targeted climate change mitigation and adaptation measures should be taken in both urban and nonurban areas of Jiangsu Province. Specific public health interventions should be focused on the leading causes of death (stroke, IHD, and COPD), whose health burden will be amplified by a warming climate. [Display omitted] •A warming climate will amplify heat-related cause-specific mortality in Jiangsu.•Nonurban residents are more vulnerable to climate change than urban residents.•Climate models contribute the largest uncertainty in health impact assessment. A warming climate in the next five decades will lead to increased burden of heat-related total and cause-specific mortality in Jiangsu, China, especially in nonurban areas.